3-Month Symptom-Based Ambidirectional Follow-up Study Among Recovered COVID-19 Patients from a Tertiary Care Hospital Using Telehealth in Chennai, India. (17th December 2021) - Nesan, G Shiny Chrism Queen; Keerthana, D; Yamini, Raja; Jain, Timsi; Kumar, Dinesh; Eashwer, Ananth; Maiya, G Rakesh
Objectives: Post-COVID-19 symptoms and its features in many recovered patients are almost similar to post-severe acute respiratory syndrome. The study aims to assess the outcome and manifestations during post-COVID follow-up period in recovered patients. Methods: Ambidirectional longitudinal study was conducted among recovered COVID-19 patients from a tertiary care hospital near Chennai through telephonic interview after discharge. Total admitted patients from June to November 2020 were 3496 and among those 183 died and 12 transferred to other hospitals. Totally 1354 consented for study and the rest were wrong numbers or not willing to participate. Chi-square test and multinominal logistic regression analysis were done. Results: Majority of, that is, 27.6% and 18.7% were in 21–30 years and >60 years, respectively. Majority were admitted with fever (38.3%), cough (15.3), and body pain (10%). Post-COVID symptoms reported were fatigue (39.7%), stress and anxiety (27.6%), and mood changes (5.8%). Some patients were newly diagnosed with diabetes mellitus (10), hypertension (5), and TB (1) after discharge. Having diabetes mellitus is an independent risk to have neurological and cardio-respiratory symptoms and patients who were discharged with minimal support were to have an independent risk factor of renal symptoms on follow-up than other subjects. Conclusion: The follow-up symptoms were associated with the patients' comorbidities, age, severity of illness, and environmental factors.